The challenges of employing one of the techniques of the Fourth Industrial Revolution (augmented reality) in teaching science from the point of view of female teachers the second field in Sharqiyah South Governorate - Al-Mashaikhi, Basma Nasser Mohammed; Mai, Mohammed (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to reveal the challenges that face female teachers in the second field in applying one of the techniques of the Fourth Industrial Revolution (augmented reality). The study included teachers in the second field of schools in the South Sharqiyah Governorate, and the study relied on the descriptive survey approach in obtaining information, and the questionnaire was used as a tool to collect data using Google Forms. The study sample, which was chosen randomly, consisted of 196 teachers. The results of the study showed the existence of organizational challenges. On the other hand, the material and technical challenges came with a very high degree to apply (augmented reality) technology. In light of the results, the study recommends the need to guide the teacher using Techniques of the Fourth Industrial Revolution (Augmented Reality) by building curricula that support the employment of technology, preparing schools with devices and the Internet to keep pace with modern technologies, and developing the performance of second field teachers by attaching They are taking intensive training courses on the techniques of the Fourth Industrial Revolution (Augmented Reality).
Keywords: The Fourth Industrial Revolution; Augmented Reality; Female teachers in the second field